2009
DOI: 10.1136/jech.2008.079038
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity is related to a green living environment

Abstract: Background: As a result of increasing urbanisation, people face the prospect of living in environments with few green spaces. There is increasing evidence for a positive relation between green space in people's living environment and self-reported indicators of physical and mental health. This study investigates whether physicianassessed morbidity is also related to green space in people's living environment. Methods: Morbidity data were derived from electronic medical records of 195 general practitioners in 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
608
3
35

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 910 publications
(737 citation statements)
references
References 24 publications
35
608
3
35
Order By: Relevance
“…A survey of 3,000 Finnish participants found that those who reported spending more of their leisure time engaged in nature-based recreational activities had higher emotional wellbeing than those who reported spending less of their free time in nature (Korpela, Borodulin, Neuvonen, Paronen, & Tyrväinen, 2014). A series of large-scale European studies based on data from national surveys has investigated the influence of nearby green space on wellbeing and mental health (de Vries, Verheij, Groenewegen, & Spreeuwenberg, 2003;Maas et al, 2009;Van den Berg et al, 2010;White, Alcock, Wheeler, & Depledge, 2013). These studies consistently find that living in an area with more green space is associated with less mental distress than living in an area with less green space.…”
Section: Nature and Hedonic Wellbeingmentioning
confidence: 86%
“…A survey of 3,000 Finnish participants found that those who reported spending more of their leisure time engaged in nature-based recreational activities had higher emotional wellbeing than those who reported spending less of their free time in nature (Korpela, Borodulin, Neuvonen, Paronen, & Tyrväinen, 2014). A series of large-scale European studies based on data from national surveys has investigated the influence of nearby green space on wellbeing and mental health (de Vries, Verheij, Groenewegen, & Spreeuwenberg, 2003;Maas et al, 2009;Van den Berg et al, 2010;White, Alcock, Wheeler, & Depledge, 2013). These studies consistently find that living in an area with more green space is associated with less mental distress than living in an area with less green space.…”
Section: Nature and Hedonic Wellbeingmentioning
confidence: 86%
“…In a context of rapid urbanization at the global scale, there is growing interest in the relationships between green spaces and health (Bowler et al, 2010;Lee and Maheswaran, 2011;Maas et al, 2009). Greenness exposure has been associated with reductions in risks of various health outcomes, including self-perceived health (Maas et al, 2006;Mitchell and Popham, 2007), blood pressure (Agyemang et al, 2007) and mortality (Villeneuve et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that access to UGS is associated with many health benefits for children. Studies, for instance, show that children who live in greener surroundings or have views of and access to green environments are healthier (Grahn, 1996), cope better with stressful life events (Wells and Evans, 2003), have lower rates of depression (Maas, et al, 2009), less stress and anxiety (Chawla, et al, 2014), reduced symptoms of attention deficit disorder (ADD) and attention deficit hyperactivity disorder (ADHD) (Kuo and Faber Taylor, 2004;Faber Taylor and Kuo, 2009), and higher self-discipline (Faber Taylor, et al, 2002), and show more focused attention (Grahn, 1996;Wells, 2000) and reduced inattentiveness (Dadvand, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%